Negative dramaturgies and the development of productive negation - Hartmann, Zee (Department of Drama, 2020)
The content of this dissertation is a cognitive map of divergent methodologies that contributed to the creation of a practice based on physical and conceptual, academic and non-academic, modes of knowledge-making and knowledge-gathering. I will show how the act of negating, whether verbally or through conceptual strategies, elucidates the untapped potential of dance- or theatre-making processes. Weaving together a collection of ideas by academics, thinkers and makers from a variety of disciplines, together with the design of my own negative dramaturgy (which I have preliminarily coined here as Productive Negation), I aim to bring the omniscient negativity of dramaturgy into focus as a mobilizing, dynamic strategy for invention. The act of negation embodies a powerful force of conviction that clarifies muddled subjectivity popular in art criticism today, and yet it leaves enough room for focused investigation. This can be seen in the proposed four-step working model of Productive Negation based on Liz Lerman’s Critical Response Process. Far from being an in-depth discourse on theories of negation, Productive Negation is a methodology that attempts to marry theoretical and practical applications through the interpretive voice of the dramaturg in a collaborative environment.